La formación artística del profesorado para el desarrollo de proyectos colaborativos en la educación primaria - García, Maria Begoña Paz (2017)
The education sector is undergoing a significant transformation in which the art education is present because of its interdisciplinary nature. Consequently, it is essential to train teachers in the plastic and visual expressions. As artists and teachers, we present three educational experiences with working groups in order to show the strengths and the opportunities of an art training in proceedings, processes and resources, enabling teachers to automatically develop different collaborative projects in the classroom